2022
DOI: 10.1101/2022.11.09.515770
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sodium channel endocytosis drives axon initial segment plasticity

Abstract: Activity-dependent plasticity of the axon initial segment (AIS) endows neurons with the ability to adapt action potential output to changes in network activity. Action potential initiation at the AIS highly depends on the clustering of voltage-gated sodium channels, however the molecular mechanisms regulating their plasticity remain largely unknown. Here, we used novel genetic tools to endogenously label sodium channels and their scaffolding protein, to reveal their nanoscale organization and longitudinally im… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Strikingly, not only non-physiological conditions such as high extracellular potassium (Grubb and Burrone, 2010;Evans et al, 2015), but also network stimulations in a physiological context, resulted in rapid AIS shortening (Jamann et al, 2021). Likewise, a recent study reported an NMDA-receptor-dependent reduction in AIS length within half an hour after induction of chemical long-term depression (Fréal et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, not only non-physiological conditions such as high extracellular potassium (Grubb and Burrone, 2010;Evans et al, 2015), but also network stimulations in a physiological context, resulted in rapid AIS shortening (Jamann et al, 2021). Likewise, a recent study reported an NMDA-receptor-dependent reduction in AIS length within half an hour after induction of chemical long-term depression (Fréal et al, 2022).…”
Section: Discussionmentioning
confidence: 99%